Tuberculosis with relapse: A model. Issue 1 (2nd January 2017) - Yang, Yali; Wu, Jianhong; Li, Jianquan; Xu, Xiaxia
ABSTRACT: In a model of tuberculosis with relapse, the basic reproduction number R 0 includes new and relapse infections. Lyapunov functions help to prove that the global dynamic is completely determined by R 0 . Replicated Latin hypercube sampling shows that early diagnosis and treatment are more efficient when relapse cases are considered.